Critical Synthesis Package: Brief COPE Questionnaire - Abbey K. Valvano; Lara Stepleman (Association of American Medical Colleges, 2013)
Abstract This Critical Synthesis Package contains: (1) a Critical Analysis of the psychometric properties and application to health sciences education for the Brief COPE Questionnaire, and (2) a copy of the Brief COPE Questionnaire and instructions developed by Charles Carver, PhD. The Brief COPE is a 28-item measure of situational and dispositional coping styles and includes 14 two-item scales labeled: Self-Distraction, Active Coping, Denial, Substance Use, Use of Emotional Support, Use of Instrumental Support, Behavioral Disengagement, Venting, Positive Reframing, Planning, Humor, Acceptance, Religion, and Self-Blame. It has been used with samples of medical students, nursing students, communities affected by a natural disaster, caregivers, and patients. The Brief COPE is available in English, Spanish, French, Greek, and Korean. It is a flexible tool, as the instructions and item language may be adjusted to fit the researchers' needs, and researchers may choose those scales most appropriate for their work. Some subscales of the Brief COPE have less support than others. It should be noted, however, that high internal consistency may be difficult to achieve given that the scales consist of only two items each. Caution should be used when interpreting results of the Brief COPE, as this measure assumes that individuals are accurate reporters of their own coping styles. Such accuracy depends, in part, on self-awareness as well as the impact of social desirability on item responses. While the Brief COPE subscales have been combined in some studies to create broader categories of coping styles, further research is needed to adequately evaluate the psychometric properties of these scales.